Designing community-based breeding strategies for indigenous sheep breeds of smallholders in Ethiopia - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This project will develop and test community-based breeding strategies for resource poor sheep owners in the highlands of Ethiopia. It will operationalize a rising approach in genetic improvement of livestock breeds that necessitates the involvement of local communities and institutions in the design of breeding strategies and implementation of resulting programs. Among its expected results are the definition of breeding goals through participatory manner by farmers and at least one breeding program established per breed; and a methodological framework for the development of community based breeding programs for smallholder producers, including institutional arrangements.